24.1% External Quantum Efficiency of Flexible Quantum Dot Light‐Emitting Diodes by Light Extraction of Silver Nanowire Transparent Electrodes. Issue 19 (5th July 2018) - Ding, Ke; Fang, Yunsheng; Dong, Shaohua; Chen, Hongting; Luo, Beibei; Jiang, Kui; Gu, Honggang; Fan, Lianwei; Liu, Shiyuan; Hu, Bin; Wang, Lei
Abstract: Flexible quantum dot light‐emitting diodes (FQLEDs) always suffer poor performance, and current efforts towards performance improvement need complicated procedures but still ending with limited progress. An extremely efficient and simply structured FQLED is demonstrated profited from the substantially enhanced light outcoupling efficiency by employing solution‐processed flexible silver nanowires (AgNWs) transparent conductive electrodes (TCEs). As is uncovered by rigorous simulations, AgNWs TCEs extract enormous light trapped in the substrate mode and waveguide mode compared with indium tin oxide (ITO) TCEs, which greatly agrees with the experimental measurements in this work. As an ultimate achievement, the FQLED shows the record‐breaking maximum external quantum efficiency of 24.1% and current efficiency of 19.5 cd A −1, giving a ≈4.4 and 3 times efficiency improvement compared to the rigid QLED with glass/ITO, respectively. This study not only demonstrates the prominent role of network‐based TCEs for efficient ITO‐free FQLEDs, but also shows a lot of room for further performance improvement of flexible light‐emitting devices with the guideline of light extraction by solution‐processed electrodes. Abstract : A fairly efficient flexible quantum dot light‐emitting diode (FQLED) is demonstrated, by using polyimide/silver nanowires (PI/AgNWs) as flexible transparent conductive electrodes (TCEs) and light extraction medium simultaneously. The FQLED with PI/AgNWs TCEs shows the record‐breaking maximum external quantum efficiency of 24.1%.